Mapping User Experience Information Overload Problems Across Disciplines - Kusuma, Wahyu Andhyka; Jantan, Azrul Hazri; Abdullah, Rusli bin; Admodisastro, Novia; Mohd Norowi, Noris binti (JOIV : International Journal on Informatics Visualization, 2023)
User Experience (UX) has been increasing linearly with the systems and digital media. UX concept describes a human factor as an experience with the life cycle of digital technology. UX increases the usability of the product in the industry more than functionality. Interest in UX has produced a huge amount of product and research articles. Moreover, this interdisciplinary topic becomes increased significantly because of the wider applications. However, this benefit become a problem due to the number of publications. The information overload problem is the result of the increasing UX topic. Several researchers solved this problem with qualitative analysis, but it cannot solve the overload problem. In this paper, we purposed bibliometric analysis and research profiling to interpret UX information on the map, with the publications from 1998-2022, a dataset compiled in RIS format to provide article metadata. As a result, the UX information map from the topic with the five clusters. Therefore, to provide information on the topic's coherence, we propose a coupling network. A related topic is shown as a link; a direct link means high coherence between topics. The analysis was carried out using the 5W1H approach (what, where, who, when, why, and how). The results show that UX is indeed an interdisciplinary field, especially with a design approach and user experience. In addition, to determine novice researchers, determining the focus of research can be done by taking into account previous research goals and maps.